2022
DOI: 10.1155/2022/3689344
|View full text |Cite|
|
Sign up to set email alerts
|

Nursing Methods and Experience of Local Anesthesia Patients under Arthroscope

Abstract: In order to solve the nursing problems of local anesthesia patients under arthroscopy, a nursing method and experience based on local anesthesia patients under arthroscopy was proposed. From June 2019 to May 2021, 478 patients who underwent knee arthroscopy under spinal anesthesia or local anesthesia were retrospectively investigated, including 186 cases (38.9%) under local anesthesia and 292 cases (61.1%) under spinal anesthesia. 2% lidocaine plus epinephrine was injected locally and intra-articular in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%